Protective effect of calcium nanophosphate and CPP-ACP agents on enamel erosion - Fabiola Galbiatti de Carvalho; Veruska Lima Moura Brasil; Tiago Joao da Silva Filho; Hugo Lemes Carlo; Rogerio Lacerda dos Santos; Bruno Alessandro Silva Guedes de Lima (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this study was to assess the effect of different remineralizing agents on enamel microhardness (KHN) and surface topography after an erosive challenge. Forty-eight human enamel specimens (4 × 4 mm) were randomly assigned to 4 groups: control (no treatment), fluoride varnish, calcium nanophosphate paste and casein phosphopeptide-amorphous calcium phosphate paste (CPP-ACP). Both pastes were applied for 5 minutes, and ﬂuoride varnish, for 24 h. Four daily erosive cycles of 5 minutes of immersion in a cola drink and 2 h in artiﬁcial saliva were conducted for 5 days. KHN readings were performed at baseline and after 5 days. The percentage of enamel hardness change (%KHN) was obtained after erosion. The surface topography was evaluated by atomic force microscopy (AFM). The data were tested using ANOVA, Tukey's and paired-T tests (p < 0.05). After an erosive challenge, there was no statistically signiﬁcant difference between the control (96.8 ± 11.4 KHN / 72.4 ± 3.0 %KHN) and the varnish (91.7 ± 14.1 KHN / 73.4 ± 5.5 %KHN) groups. The nanophosphate group showed lower enamel hardness loss (187.2 ± 27.9 / 49.0 ± 7.9 %KHN), compared with the CPP-ACP group (141.8 ± 16.5 / 60.6 ± 4.0 %KHN), and both were statistically different from the varnish and the control groups. AFM images showed a rough surface for the control and the varnish groups, a non-homogeneous layer with globular irregularities for CPP-ACP, and a thick homogeneous layer for the nanophosphate group. None of the agents provided protection against the development of erosion; however, nanophosphate paste was able to reduce enamel surface softening after the erosive challenge